Neurodevelopmental, Mental Health, and Parenting Issues in Preterm Infants - Richard J. Shaw; Soudabeh Givrad; Celeste Poe; Elizabeth C. Loi; Margaret K. Hoge; Melissa Scala (MDPI AG, 2023)
The World Health Organization in its recommendations for the care of preterm infants has drawn attention to the need to address issues related to family involvement and support, including education, counseling, discharge preparation, and peer support. A failure to address these issues may translate into poor outcomes that extend across the lifespan. In this paper, we review the often far-reaching impact of preterm birth on the health and wellbeing of the parents and highlight the ways in which psychological stress may have a negative long-term impact on the parent-child interaction, attachment, and the styles of parenting. This paper addresses the following topics: (1) neurodevelopmental outcomes in preterm infants, including cognitive, sensory, and motor difficulties, (2) long-term mental health issues in premature infants that include elevated rates of anxiety and depressive disorders, autism, and somatization, which may affect social relationships and quality of life, (3) adverse mental health outcomes for parents that include elevated rates of depression, anxiety, and symptoms of post-traumatic stress, as well as increased rates of substance abuse, and relationship strain, (4) negative impacts on the parent-infant relationship, potentially mediated by maternal sensitivity, parent child-interactions, and attachment, and (5) impact on the parenting behaviors, including patterns of overprotective parenting, and development of Vulnerable Child Syndrome. Greater awareness of these issues has led to the development of programs in neonatal mental health and developmental care with some data suggesting benefits in terms of shorter lengths of stay and decreased health care costs.